Dampak Covid 19 Terhadap Bank Syariah - Ihsan Effendi; Prawidya Hariani RS (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
Covid-19 has really worried people today. The impact has been felt in various sectors of public life, including the financial sector. Many sectors that have been carried away by the current economic crisis, one of the impacts is Islamic financial institutions. This research is intended to look at the resilience of Islamic banks during this pandemic, especially Islamic commercial banks (BUS) and Islamic business units (UUS). One of the indicators of the resilience of Islamic banks is Return on Assets (ROA), non-performing finance (NPF) and financing to deposit ratio (FDR) during the pandemic period, namely from July 2019 to June 2020. The results of this study indicate that ROA has decreased significantly. , whereas the NPF and FDR are still within safe limits.